151k views
1 vote
Can someone please help me on this problem? I don’t know how to do it!!!

Can someone please help me on this problem? I don’t know how to do it!!!-example-1
User Ma
by
5.1k points

1 Answer

4 votes

Answer:

(x^(11/4))(y^(5/9))

Explanation:

The applicable rules of exponents are ...

(x^a)(x^b) = x^(a+b)

(x^a)/(x^b) = x^(a-b) . . . . . no surprise, since 1/x^b = x^-b

_____

Your expression simplifies to ...

x^((5/4) -(-5/4) -(-1/4)) · y^((1/18) -(-1/2))

= x^(5/4 +5/4 +1/4) · y^(1/18 +1/2)

= x^(11/4) · y^(1/18 +9/18)

= x^(11/4) · y^(5/9)

User Rafael Neto
by
5.3k points